Analysis of the Influence of Work Engagement and Work-Life Balance on Employee Productivity through Employee Well-Being in the Service Industry with a Hybrid Work Environment - Alamudi, Abdul Kadir (Management Analysis Journal, 2025)
This research aims to analyze the effects of work engagement and work-life balance on employee productivity, with employee well-being as a mediating variable. The background of this research is based on changes in work models that now widely adopt a hybrid work system, especially in the service industry. This study uses a quantitative approach with an explanatory research design. A total of 400 respondents working in a hybrid manner in the service industry in the Surabaya area were selected using the Lemeshow method. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on SmartPLS. The results show that work engagement has a positive and significant impact on work productivity and employee well-being. Work-life balance does not have a significant effect on work productivity, but it has a significant effect on employee well-being. Employee well-being has a significant positive impact on work productivity and serves as a significant mediating variable between work engagement and work-life balance on productivity. This study suggests the importance of improving employee well-being as a way to enhance productivity in a hybrid work system.